2021
DOI: 10.3390/ani11041172
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of a Sheep Population in Oaxaca, Mexico: The Chocholteca Creole

Abstract: Creole sheep in México have undergone crossbreeding, provoking the loss of genetic variability. The objective of the present study is to determine the intra-racial genetic diversity, the genetic relationship with other genotypes, and the populational substructure of the Oaxacan Creole sheep. Twenty-nine blood samples were obtained of Creole sheep of the Oaxaca Mixteca region in México. A genetic analysis was made with 41 microsatellites recommended for studies of genetic diversity in sheep. An analysis was mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…All analyzed markers had PIC values greater than 0.5 or on average 0.781, which indicates a high diversity of the studied sheep population and the reliability of the used set of markers for the study of genetic diversity. The PIC value obtained in our study is higher than that reported by Girish et al [ 11 ] and Salinas-Rios et al [ 19 ] but lower than that reported for 12 Algerian sheep breeds [ 18 ].…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…All analyzed markers had PIC values greater than 0.5 or on average 0.781, which indicates a high diversity of the studied sheep population and the reliability of the used set of markers for the study of genetic diversity. The PIC value obtained in our study is higher than that reported by Girish et al [ 11 ] and Salinas-Rios et al [ 19 ] but lower than that reported for 12 Algerian sheep breeds [ 18 ].…”
Section: Discussioncontrasting
confidence: 83%
“…These results are in accordance with results obtained for the group of autochthonous breeds from the Balkan Peninsula [ 12 ], Kazakh sheep breeds [ 17 ], some Croatian local breeds that belong to the group of coarse-wool Pramenka breeds [ 45 ], as well as Jordan and Arabian sheep breeds [ 43 , 46 ]. A higher diversity of the sheep population in terms of the average Ho and PIC was reported for 12 Algerian sheep breeds [ 18 ] and 14 Iran sheep breeds [ 47 ], and a lower diversity of the sheep population was obtained by many researchers [ 15 , 19 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the American continent, Creole sheep represent a strategic genetic resource for populations living in marginal areas with scarce economic resources [ 1 , 2 , 3 ]. They also represent an essential role in the family economy since they provide high-quality meat, wool and, leather to local populations [ 4 , 5 , 6 ]. The term creole (criollo in Spanish or crioula in Portuguese) refers to the Iberian descendants in the Americas, including cattle and sheep [ 2 ].…”
Section: Introductionmentioning
confidence: 99%